The impact of corporate governance elements on environmental reporting : the case of public listed companies in Malaysia / Mohd Rashdan Sallehuddin - Sallehuddin, Mohd Rashdan (Research Management Institute (RMI), 2014)
The paper aims to examine the impact of the relationship between the elements of corporate governance and environmental reporting of public listed companies in Malaysia. This study adopts a cross sectional analysis by examining the 2010 annual reports of 254 public listed companies and using content analysis as the method to measure the extent of environmental reporting and compared with various corporate governance measures. Regression analysis was used to examine the relationship between Corporate Environmental Reporting (CER) and independent variables of Corporate Governance (CG) namely independent non-executive directors, audit committee composition, female director, duality, managerial and government ownership. Analysis found a significant relationship between the extents of environmental reporting with government ownership. In contrast, the extent of CER is insignificant with relation of independent non-executive directors, audit committee composition, female director, duality and managerial ownership. The results could be useful to provide evidence to regulatory bodies to look further and to identify the elements of corporate governance that will enhance the CER.